A Review of the Utility of Mother Tinctures and Low Potencies in Indigestion (Homoeopathy for All, 2022)
Now and then, we come across  the complaint of indigestion in  our routine. As the name suggests,  indigestion means impaired  digestion. For some, this word  implies symptoms like heartburn  or regurgitation, which form a part  of gastroesophageal reflux disease  (GERD). In addition, it may relate to  belching, foetor oris or foul breath,  localized pain, and discomfort  in the epigastrium, among many  others. According to the medical  literature, indigestion is also called  dyspepsia. It is a functional disorder  of the gastrointestinal system.  This article is an outlook on the  condition and its management  through an uncommon aspect of  mother tinctures and low potencies,  which have been mentioned often in  the homeopathic literature but are  infrequent in practice.
Keywords: indigestion; localized; potencies